Peningkatan Keterampilan Pemeriksaan Kesehatan Pengukuran Tekanan Darah dan Kadar Hemoglobin pada Palang Merah Remaja untuk Pencegahan Stunting secara Peer Group - Wirata, Resta Betaliani; Sinaga, Mei Rianita Elfrida; Adiyasa, Ratna Puspita (Kisi Berkelanjutan: Sains Medis dan Kesehatan, 2025)
This community service program aims to enhance the skills of Youth Red Cross (PMR) members in measuring blood pressure and hemoglobin levels through the peer group method. The program was conducted in October 2024, involving 23 PMR members. The implementation of this community service followed several stages: socialization, training, technology application, mentoring and evaluation, and program sustainability. The application of technology in this program utilized the peer group method. Following the training activities, results showed that 100% of participants were able to measure blood pressure, and 91.3% were able to measure hemoglobin levels. This community service program successfully improved the competency of PMR members in conducting screening or early detection among peers. The implications for preventing hypertension and anemia include reducing the risk of stunting in future generations and motivating participants to become healthy and responsible leaders. Based on these findings, it is recommended to continue implementing health screening activities using the peer group approach. Achieving Sustainable Development Goals (SDGs) This community service program focuses on preventing stunting in the future through screening and early detection among adolescents by involving PMR youth groups in peer group activities. This article contributes to SDG Goal 3: Ensure healthy lives and promote well-being for all at all ages. The targeted indicator is Target 3.4, which aims to reduce premature mortality from non-communicable diseases by one-third by 2030 through prevention, treatment, and the promotion of mental health and well-being.